The Oxford Handbook of Law and Politics 2009
DOI: 10.1093/oxfordhb/9780199208425.003.0017
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Law and American Politics

Abstract: Public law scholars whose scholarship focuses primarily on the public conflicts between constitutional authorities fail to appreciate how constitutional law influences politics and judicial decision making in the United States. Legal norms better explain how constitutional controversies are structured than how they are resolved. Basic principles of constitutional law help secure legal agreement in the face of political disagreement. When political disagreements are resolved into legal disagreements, basic prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…National newspapers are more likely to feature federal officials, who are more likely to frame the pandemic in broader terms of the threat it poses to the nation, instead of specific communities, which is of less salience to a national audience. These two reasons are also deeply intertwined, as national-level officials focus their attention on aspects of the issues that they care about and on reaching national-level audiences, just as local officials do the same with local-level issues and audiences (Graber 2009).…”
Section: Local and National Framing Of Immigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…National newspapers are more likely to feature federal officials, who are more likely to frame the pandemic in broader terms of the threat it poses to the nation, instead of specific communities, which is of less salience to a national audience. These two reasons are also deeply intertwined, as national-level officials focus their attention on aspects of the issues that they care about and on reaching national-level audiences, just as local officials do the same with local-level issues and audiences (Graber 2009).…”
Section: Local and National Framing Of Immigrationmentioning
confidence: 99%
“…These are less likely to become a focus of national coverage, as these audiences have been found to be more focused on issues of national significance (Price, and Zaller 1993). Audiences for local news tend to be more interested in issues immediately impacting them, which influences both what is reported and how larger problems are framed (Graber 2009). Support for this is demonstrated by Mourão et al (2021), who found significant differences between local and national newspapers in the framing of the 2014 protests in Ferguson.…”
Section: Local and National Framing Of Immigrationmentioning
confidence: 99%
“… I find the recent essay by Thomas Keck (2007) especially clear and useful. Also see Graber (forthcoming). …”
mentioning
confidence: 95%
“…In doing so, and in criticizing other opinions as excessively political, scholars of the judicial process have evinced a need to understand how the judicial mode of governance relates to the legislative, executive, and administrative modes and to principles of popular governance more generally. Especially in the politically charged arena of constitutional review, scholars have sought to understand how different public actors interact to establish the meaning of the Constitution (Keck 2007; Whittington 2007; Leonard 2002; Kramer 2004; Graber forthcoming). And in some cases that means that we want to know when the judiciary has exercised (or usurped) authority plausibly claimed by some other institution or process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation